Steroid injection versus NSAID injection for trigger finger: a comparative study of early outcomes - Shakeel, H; Ahmad, T.S. (Elsevier, 2012)
PURPOSE: Stenosing tenosynovitis of the flexor tendon sheath of the digits of the hand results from a discrepancy between the diameter of the flexor tendon and its sheath at the A1 pulley. The treatment options for trigger digits include oral nonsteroidal anti-inflammatory drugs (NSAIDs) and local NSAID applications, splintage, steroid injection, and percutaneous and open release of the A1 pulley. Injectable NSAID is used intramuscularly and locally in other sites. The hypothesis is that an injectable NSAID is as effective as the traditionally used steroid injection in the treatment of trigger digit, based on Quinnell grading, and that the treatment works as well in patients with diabetes as in those without diabetes.